2020
DOI: 10.31729/jnma.4892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infestation among Public School Children of a Community

Abstract: Introduction: Intestinal parasitic infestation is one of the major health problems in developingcountries like Nepal. This study was done to determine the prevalence rate of intestinal parasiticinfestation among school children in Duwakot VDC, Bhaktapur, Nepal. Methods: A descriptive cross-sectional study was done in 194 public school children of Duwakotvillage development committee from August to October, 2019. Ethical clearance was obtained fromthe Institutional Review Committee (reference no. 12072019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
3
8
0
3
Order By: Relevance
“…In contrast, different study reports of Dharan, Nepal had shown 40% (Poudyal et al, 2017) and 11.5% (Gyawali et al, 2010) prevalence of G. lamblia which is dissimilar with our findings. In Kathmandu, the overall prevalence of Hookworm was found to be 23.7% (Sharma et al, 2004) which agreed with our…”
Section: Association Of Socio-demographic Factors With Intestinal Parasite Infectionssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, different study reports of Dharan, Nepal had shown 40% (Poudyal et al, 2017) and 11.5% (Gyawali et al, 2010) prevalence of G. lamblia which is dissimilar with our findings. In Kathmandu, the overall prevalence of Hookworm was found to be 23.7% (Sharma et al, 2004) which agreed with our…”
Section: Association Of Socio-demographic Factors With Intestinal Parasite Infectionssupporting
confidence: 91%
“…In this study, male participants were found to be more likely to be infected with parasites with a 9.37% (6/64) prevalence than the female with a 5.76% (3/52) prevalence but the difference was not significant (p=0.47). The finding was consistent with the other studies in Dharan (Gyawali et al, 2010) and Kathmandu (Sharma et al, 2004), however, incompatible with previous studies done in Dhankuta (Shakya, 2003) and Itahari (Sah, Bhattarai, et al, 2013). It reflects that gender may not play the role in IPIs but may depend on sanitation conditions and hygiene practices.…”
Section: Handwashing After Defecationsupporting
confidence: 84%
See 1 more Smart Citation
“…El microorganismo más frecuente fue Giardia lamblia en 22 casos (11,34%), las infecciones helmínticas fueron 2 casos (1,03%), ocasionadas por Hymenolepis nana y Hookworm, respectivamente. Este estudio fue realizado en Nepal en donde se ha observado un descenso considerable de parasitismo infantil en los últimos años (Sharma et al, 2020), difiriendo por completo con los resultados descritos en esta investigación. En Ecuador no se ha observado un decrecimiento de la prevalencia parasitaria, por lo cual, se sugiere prestar mayor atención a este problema de salud pública, sobretodo por los entes de control y salud pública.…”
Section: Discussionunclassified
“…Los síntomas producidos por la parasitosis sobre el hospedero van de leves a graves, entre ellos destacan color de piel pálido, dolor abdominal, diarrea, retraso en el crecimiento y hemorragia digestiva; afectando notablemente la calidad de vida de los niños (Jerez-Puebla et al, 2020;Palacios, 2017;Sharma et al, 2020;Vidal-Anzardo et al, 2020). Cuando ocurren de forma masiva, incrementan de forma considerable el riesgo de muerte.…”
Section: Introductionunclassified